2019
DOI: 10.1177/1757177419855603
|View full text |Cite
|
Sign up to set email alerts
|

Nebuliser cleaning and disinfection practice in the home among patients with cystic fibrosis

Abstract: Background: Nebulised delivery of different classes of drugs is of fundamental importance in therapeutic regimens relating to both the management of disease progression in cystic fibrosis disease and its associated complications. The aim of this study was to determine if current nebuliser hygiene practices in the home environment by paediatric and adult cystic fibrosis populations are appropriate to ensure appropriate infection control and prevention measures have been addressed. Methods: An Audit Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…1 The delivery of nebulized therapy is an important component of the care in patients with CF, in which this modality is used to effectively deliver, mainly, antibiotics and mucolytic agents. 2 Proper maintenance of the nebulizer in terms of ensuring that its performance is maintained optimally as well as ensuring that devices are effectively cleaned and disinfected becomes an important element of nebulized therapies.…”
Section: Introductionmentioning
confidence: 99%
“…1 The delivery of nebulized therapy is an important component of the care in patients with CF, in which this modality is used to effectively deliver, mainly, antibiotics and mucolytic agents. 2 Proper maintenance of the nebulizer in terms of ensuring that its performance is maintained optimally as well as ensuring that devices are effectively cleaned and disinfected becomes an important element of nebulized therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, none of the adult patients reported disinfecting nebulizers on a daily basis. 20 Even though only 5 of 22 adult patients were primarly responsible for nebulizer care in our study, nebulizer disinfection frequency after each use or daily was only 22.7% in the entire adult group. These results may suggest that adult patients may need more attention and support for adherence to treatment, especially before transition from pediatric to adult care.…”
Section: Discussionmentioning
confidence: 52%
“…There have been numerous reports of nebuliser hygienic practices in the home that have highlighted that each individual has their own ideas about how to clean and disinfect their nebuliser in terms of frequency of cleaning, washing, drying, disinfection and storage of nebulisers [ 7 , 14 , 15 , 24 ]. One of the earliest studies concluded that respiratory therapists should immediately address and improve their nebuliser cleaning methods and replacement practices with more focus on teaching patients these practices [ 25 ].…”
Section: Experiences Of Nebuliser Hygiene At Homementioning
confidence: 99%